THE CHILD’S WORLD IN CHORNOBYL STORIES FOR CHILDREN BY YEVHEN HUTSALO - Derkachova, Olga; Boichuk, Alla (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
In the article, the stories of Yevhen Hutsalo from the collection "Children of Chornobyl" are analyzed, and the peculiarities of portraying the world of a child after the Chornobyl disaster are highlighted. The thematic scope of these works is outlined, which shows the consequences of this tragedy through the forced and irreversible changes that the characters experience and live through. Among them are the loss of their homes, friends, and parents. The following groups of characters are distinguished: those who have lost their world (Palma, Kalyna, Mykolka, Katrya), those who help these heroes (Hrytsko, Liubomyr), and those who are indirectly affected by the Chornobyl disaster (Savka-Savka, Olena, Mariana, Hanna Mykhailivna). It is noted that the past, lost world of the characters is practically unspoken and is mentioned episodically by one or two lines of dialogue from the characters, while the present world is a narrative of losses and loneliness. It is a world without loved ones, who are taken away either by death or forced searches for work. For the youngest characters, it is fragile and fleeting (Kalyna's illness, preparation for Katrya's death, Savka-Savka's death). The conclusions are drawn that the world of the young hero in these works is a world after loss, in which their future is unclear and uncertain. For adult characters, it is a world of fear due to a lack of understanding of possible consequences of environmental disasters. The only salvation and interlude between anxieties and fears is nature, in harmony with which the characters are filled with adventures, quiet joy, and peace. The following works are analyzed: "Mad Chornobyl Dog," "Chornobyl Girl Kalyna," "Crying in the Dark Night," "Rudnya," "Zozulya," "Child of Strontium," and “Christmas Story”.